TO ASSESS THE EFFECTIVENESS OF FIRST-LINE XELOX COMBINED WITH BEVACIZUMAB IN PATIENTS WITH STAGE IV COLORECTAL CANCER TREATED AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the effectiveness of first-line XELOX combined with Bevacizumab in patients with stage IV colorectal cancer treated at Nghe An Oncology Hospital.Subjects and methods: A retrospective descriptive study with prospective longitudinal follow-up was conducted in 54 patients with stage IV colorectal cancer who received first-line XELOX plus Bevacizumab at Nghe An Oncology Hospital between January 2022 and September 2025.Results: Among the 54 enrolled patients, the objective response rate and disease control rate after four treatment cycles were 50% and 90.7%, respectively. Following eight cycles, the objective response rate was 34.8%, while the disease control rate remained at 71.7%. The median PFS was 9.8 months (95% CI: 7.3-11.0 months), with estimated 6-month and 12-month PFS rates of 77.3% and 33.0%, respectively. Patients with well- or moderately differentiated tumors experienced significantly longer PFS than those with poorly differentiated, mucinous, or signet-ring cell carcinomas (10.6 vs. 6.7 months; p = 0.02). Likewise, patients with metastasis confined to a single organ achieved superior PFS compared with those presenting with metastases in two or more organs (9.8 vs. 5.1 months; p = 0.012). Adverse events were predominantly grade 1-2. The most common adverse events were hand-foot syndrome (37%), peripheral neuropathy (35.2%), leukopenia (33.3%), and Bevacizumab-associated hypertension (11.1%). Bevacizumab-associated hypertension occurred in 11.1% of patients.Conclusions: First-line XELOX combined with Bevacizumab demonstrated effective disease control and favorable progression-free survival outcomes in patients with stage IV colorectal cancer. Poorly differentiated, mucinous, or signet-ring cell histology and involvement of multiple metastatic organs were associated with inferior PFS. The treatment regimen was generally well tolerated, with adverse events being predominantly mild to moderate and manageable.
Keywords: Metastatic colorectal cancer, XELOX, Bevacizumab, PFS.